Physiological Characterization of Kenyan Sorghum Lines for Tolerance to Aluminium - R. K, Cheprot; T. K, Matonyei; K. K, Maritim; B. A, Were; O. G, Dangasuk; A. O, Onkware; S, Gudu (International Journal of Natural Sciences Research, 2014)
Eighty nine Kenyan sorghum lines were screened for tolerance to aluminium toxicity in nutrient solution. Relative net root growth; root tip aluminium content and variation in organic acid exudation were used to determine the tolerance or sensitivity of the sorghum lines at 148 µM Al for six days. The lines showed variable reduction in root growth under the Al stress. On the basis of the relative net root growths, three lines were tolerant, nineteen were moderately tolerant and sixty seven were sensitive to the Al stress. The tolerant lines secreted up to five times more citrate compared to sensitive lines under the Al treatment. All the lines secreted extremely low quantities of malate under aluminium stress despite a significant positive regression (R2 = 0.83) between malate secretion and relative net root growth. There was a negative regression between relative net root growth and root aluminium concentration (R² = -0.79) among the selected sorghum lines, and the sensitive lines accumulated up to three times the amount of Al compared to the tolerant lines.. The Al tolerant sorghum lines were selected for improved sorghum production in acid soil. The objectives of this study were to (i) identify Al tolerant Kenyan sorghum lines, (ii) investigate tolerance mechanisms employed by Kenyan sorghum lines against Al stress.